Unfavorable functional outcome is expected for elderly patients suffering from acute subdural hematoma even when presenting with preserved level of consciousness. (September 2019) - Sufaro, Yuval; Avraham, Elad; Alguyn, Farouq; Azriel, Amit; Melamed, Israel
Highlights: Elderly presenting with acute sub-dural hematoma and preserved level of consciousness have unfavorable outcome. Elderly who underwent immediate surgical evacuation of the hematoma (via craniotomy) seem to have slightly worse outcome. High rates of functional deterioration are expected during first year after initial injury. Abstract: Alongside an increase in life expectancy, median age of patients presenting with traumatic acute subdural hematomas (ASDH) has increased as well. Treatment guidelines are based on studies performed on relatively young patients. The optimal management of elderly (>70 years old) patients with ASDH, specifically those with relatively preserved level of consciousness, was not thoroughly investigated so far. We retrospectively examined elderly patients presented to our medical center between the years 2006–2016 with traumatic convexity ASDH and GCS of 13–15. 773 patients were included in the initial cohort and 54 patients were included in the final analysis. The mean age at presentation was 81.5 years and the means of hematoma thickness and midline shift were 15.5 mm and 6.6 mm, respectively. Patients in our cohort had an overall unfavorable outcome (mRS 5–6) of 28% and 56% at discharge and at 1 year following injury, respectively. The results were not significantly different for the subgroups of patients older than 80 years and patients with high ASA-PS. Surgical evacuation of the ASDH was undertaken in 28 patients with focal neurologic deficit and/or worsening on subsequent brain scans. At 1 year, 64% (18 patients) in the surgery group had unfavorable outcome compared to 48% (12 patients) in the conservative group. We believe that these numbers should be taken under consideration when assessing elderly patients with convexity ASDH and relatively preserved level of consciousness.